2001
DOI: 10.1046/j.1460-9592.2001.00753.x
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine intoxication in a premature neonate

Abstract: Caffeine, which has a wide range between therapeutic and toxic levels, is a widely used medication for prevention and treatment of apnoea of prematurity. Despite its safety, caffeine overdose and intoxication has been previously reported in the literature. We present a 30-day-old 28-week preterm newborn who was exposed to 300 mg.kg-1 caffeine base by mouth accidentally. The patient exhibited agitations, irritability, tachycardia, tachypnoea, diuresis, electrolyte abnormalities, hyperglycaemia and metabolic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 7 publications
0
13
0
1
Order By: Relevance
“…Case reports of accidental caffeine overdose in premature infants have described a variety of acute neurologic, cardiovascular, and metabolic abnormalities. 80 One case report described a 28-week infant who developed rhabdomyolysis while receiving standard caffeine dosing, with a caffeine level of 32.59 µg/ml. 81 Other studies, however, have reported caffeine levels of 30-40 µg/ml without significant side effects.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Case reports of accidental caffeine overdose in premature infants have described a variety of acute neurologic, cardiovascular, and metabolic abnormalities. 80 One case report described a 28-week infant who developed rhabdomyolysis while receiving standard caffeine dosing, with a caffeine level of 32.59 µg/ml. 81 Other studies, however, have reported caffeine levels of 30-40 µg/ml without significant side effects.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…In addition to treating AOP, it has been shown that caffeine reduces bronchopulmonary dysplasia, failure to extubate, and the time on mechanical ventilators [5,6]. However, caffeine was also shown to impair cerebral and intestinal blood flow velocity [7], and if it is administered improperly, such as overdosing, it might have detrimental effects on preterm infants [8,9]. Furthermore, Carnielli et al [10] showed that caffeine treatment increases energy expenditure and suggested that it might retard infant growth.…”
Section: Introductionmentioning
confidence: 99%
“…However, caffeine therapy is associated with variable side effects including tachycardia, jitteriness, and feeding intolerance in preterm infants [7]. Caffeine was also found to increase oxygen consumption and transient decrease in the rate of growth of preterm, very low birth weight, infants [2].…”
Section: Introductionmentioning
confidence: 99%